2023
DOI: 10.1093/brain/awad338
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic alterations in Parkinson’s disease: a combined 11C-yohimbine PET/neuromelanin MRI study

Chloé Laurencin,
Sophie Lancelot,
Sarah Brosse
et al.

Abstract: Degeneration of the noradrenergic system is now considered a pathological hallmark of Parkinson’s disease but little is known about its consequences in terms of parkinsonian manifestations. Here, we evaluate two aspects of the noradrenergic system using multimodal in vivo imaging in patients with Parkinson’s disease and healthy controls: the pigmented cell bodies of the locus coeruleus with neuromelanin sensitive MRI and the density of α2-adrenergic receptors (ARs) with PET using [11C]yohimbine. Thirty patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…Currently, the integrity of the noradrenergic system is studied either analyzing neuromelanin-dependent MRI signal of the small locus coeruleus-the principal origin of noradrenergic neurons of the brain, or using PET radioligands targeting receptors or transporters of noradrenalin. Interestingly, studies have rather consistently shown a dissociation of locus coeruleus integrity as measured with MRI and integrity of noradrenergic cortical terminals using PET [77,78]. A widespread cortical (motor cortex and insula) and subcortical (thalamus and putamen) reduction of NA receptors has very recently been described [78].…”
Section: Imaging Of Noradrenaline Namentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the integrity of the noradrenergic system is studied either analyzing neuromelanin-dependent MRI signal of the small locus coeruleus-the principal origin of noradrenergic neurons of the brain, or using PET radioligands targeting receptors or transporters of noradrenalin. Interestingly, studies have rather consistently shown a dissociation of locus coeruleus integrity as measured with MRI and integrity of noradrenergic cortical terminals using PET [77,78]. A widespread cortical (motor cortex and insula) and subcortical (thalamus and putamen) reduction of NA receptors has very recently been described [78].…”
Section: Imaging Of Noradrenaline Namentioning
confidence: 99%
“…Interestingly, studies have rather consistently shown a dissociation of locus coeruleus integrity as measured with MRI and integrity of noradrenergic cortical terminals using PET [77,78]. A widespread cortical (motor cortex and insula) and subcortical (thalamus and putamen) reduction of NA receptors has very recently been described [78]. NA transporters do not appear to be dramatically reduced in prodromal PD, with some evidence for moderately reduced availability of NA transporters in the sensorimotor cortex and the thalamus [79].…”
Section: Imaging Of Noradrenaline Namentioning
confidence: 99%
“…We showed previously that the density of α 2 adrenoceptors can be quantified by imaging with [ 11 C]yohimbine positron emission tomography (PET) [11]. Interestingly, a recently published study showed α 2 adrenoceptors, as measured with [ 11 C]yohimbine, are diminished in PD patients, in correlation with both motor and non-motor indices [12]. In the present study, we hypothesize that the degeneration of the LC by the loss of noradrenergic terminals is associated with the pathological slowing of EEG patterns in PD patients.…”
Section: Introductionmentioning
confidence: 99%